Fundamental Study on Sand Stabilizing Agent Incorporating With New Chemical Mixture - Kong, Ka Ming (2021)
Sand having poor geotechnical properties and the involvement of stabilization can modify it to fulfil construction purpose. The mixed sand stabilizer of hydrated lime, Class C fly ash, sodium silicate, and natural coir fibre was used for the geotechnical properties’ enhancement and structure reinforcement to the sand. In this study, coir fibre was selected as the natural fibre for sand stabilization. Natural fibre stabilization is a cost-effective and environmentally sustainable way of enhancing sand properties. The laboratory tests of unconfined compression test and direct shear test were performed to determine and evaluate the effects of lime-fly ash-sodium silicate-coir fibre-reinforced sand. The varying proportion of coir fibre and different curing periods were selected for the tests to investigate the strength development. The laboratory test results showed that the lime-fly ash-sodium silicate-coir fibre-reinforced sand mixture could significantly enhance the geotechnical properties of sand. The incorporating of 1 % coir fibre reinforcement improves the structural stability of sand particles. The curing periods of 28 days and 56 days yield the desirable strength and highest strength value. The findings of the analysis can be used as a reference for sand reinforced engineering.